ANALISIS KESULITAN BELAJAR MATEMATIKA MELALUI PERKULIAHAN LEARNING MANAGEMENT SYSTEM - Handayani, Rukmini; Purnamasari, Ratih; Sudarjat, Jaja (Jurnal Pendidikan Dasar, 2021)
The purpose of this research is to find out how difficult it is to learn mathematics through the Learning Management System lecture. The research subjects were students in semester 2 and 4 of the Elementary School Teacher Education Study Program for the Academic Year 2020/2021 who took the subjects of Basic Geometry Studies and Basic Algebraic Studies. The research location is in the Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Pakuan University, Ciheuleut, Bogor City. This research method is descriptive with a qualitative approach. The technique of collecting data in this research is by using questionnaires, interviews, and documentation. Based on the findings in the research that has been described previously, the researcher can find that the difficulties in learning mathematics through the University FKIP Learning Management System lecture are: 1). Students are less focused when taking online lectures, 2) Students consider mathematics to be a difficult subject, 3) Algebraic Studies, Matrix material is the most difficult material, 4). Students have difficulty understanding the surface area material in the study of geometry, and 5) Students find it difficult to submit assignments because of signal constraints and the stability of the LMS. So it is recommended for the university to increase the stability of the Learning Management System. Supporting lecturers are expected to be able to better organize lecture activities in the Learning Management System through the study of teaching materials according to students' needs and difficulties in learning mathematics. Keyword : Student learning difficulties, mathematics, Learning Management System